Soviet and Eastern European trade and aid in Africa - Stokke, Baard Richard (New York : F. A. Praeger, 1967)
The study presents an analysis of the economic relations which have developed between Africa and the centrally planned economies since the mid-1950's. It sets forth in macro-economic terms the scope, growth, volume, and effects these relations have had and promise to have on the development of industry and agriculture in the constituent countries of the African continent.
"The product of research done for a doctoral dissertation submitted to the Graduate Institute of International Studies of the University of Geneva."
Bibliography: p. [297]-317.
rpm 22/01/2019
Loans
Keywords: Economic assistance, Soviet; Economic assistance, East European; Soviet Union; Africa; Europe, Eastern; Africa